The association between shorter disease course and sarcopenia in women with endometriosis: a retrospective analysis of NHANES 1999–2006 - Litao Sun; Yishu Tian; Lei Ling (Scientific Reports)
Abstract Endometriosis is a common gynecological disorder that is associated with chronic pelvic pain, infertility, and metabolic complications. Sarcopenia, characterized by progressive skeletal muscle loss, predominantly affects older adults. This study explored the incidence and risk factors for sarcopenia in endometriosis patients using the NHANES dataset, which included 373 participants. Endometriosis was confirmed through self-report questionnaire, and sarcopenia was diagnosed via dual-energy X-ray absorptiometry. Covariates encompassed age, race, marital status, education attainment, poverty income ratio, smoking habits, and comorbidities. Statistical analyses were conducted using SPSS version 26.0, incorporating four multivariate regression models. The average age was 40.3 and 40.0 years in endometriotic participants with and without sarcopenia, respectively. Minority ethnicity had higher odds for sarcopenia (OR 6.00, 95% CI 1.24–29.07). A disease duration of endometriosis less than five years was associated with higher sarcopenia risk (OR 4.83, 95% CI 2.57–9.09). Conversely, lower educational levels were linked to a reduced chance of developing sarcopenia (OR 0.42, 95% CI 0.21–0.86). These findings were consistent across all regression models, indicating that ethnic minority status, higher educational attainment, and shorter disease duration are significant risk factors for concurrent sarcopenia in endometriosis patients.